KEBIJAKAN NORMALISASI DAERAH ALIRAN SUNGAI DI KAWASAN TAMAN WISATA KULINER SIMPANG MESRA KOTA BANDA ACEH - Dahlawi; Nusrat Mahfudh; Saddam Rassanjani (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The presence of the Krueng Aceh Watershed Area (DAS) holds significant importance in the ecosystem and community life, particularly in its role as a flood control channel. However, currently, the capacity of the riverbanks and embankments of the Krueng Aceh DAS has declined due to various factors, such as climate change and the exploitation of riverbank land for economic activities by the community. This research aims to identify the processes of DAS normalization policies in the Culinary Tourism Park area of Simpang Intim, Banda Aceh City, and the coordination between the Banda Aceh City Government and the Sumatra I River Basin Agency in utilizing state-owned land. This research employs a qualitative descriptive method with data sources obtained through interviews. Findings from this research indicate that the implementation of DAS normalization policies has not been optimal due to the utilization of DAS land not fully aligning with its intended purpose and not conforming to the planned land use in the Simpang Mesra Culinary Tourism Park area in Banda Aceh City. The government has not adequately monitored the management and utilization of DAS, as evidenced by the construction of permanent buildings by some culinary business owners that do not comply with regional regulations. The lack of firmness from the government towards business actors using the land also results in the non-alignment of land use with applicable regulations.